Analysis of indicators of time spent by emergency medical service team in acute coronary syndrome with elevation of st segment at the stage of direct stay on call - V. F. Zabashta; B. S. Fedak (Kazimierz Wielki University, 2021)
Urgency. The period of a patient's hospitalization from the beginning of the disease has an important role in the provision of medical care. According to the Unified Clinical Protocol for the provision of medical care to acute coronary syndrome (ACS) patients, the latter must be hospitalized to an expert healthcare center in 90-120 minutes. That is why the main areas of pre-hospital care include the rapid recognition of acute myocardial infarction (AMI), stabilization of the patient's condition and his rapid transportation to the appropriate medical institution. The time from the appearance of the first symptoms of a heart attack to the arrival of the patient in the admission department of the hospital is an important factor influencing the course of AMI in further treatment, so to reduce the loss of time at this stage is important. The aim of the study was to analyze the time spent on the implementation of the protocol of assistance in AMI with the rise of the ST segment at direct stay of the emergency team on call. Materials and methods. A questionnaire survey of 85 emergency physicians working in Kharkiv was conducted. System approach, analytical, sociological (questionnaire), computer data processing and statistical methods were used. Results and discussion. The time spent on the implementation of each item of the protocol of medical care in ACS with elevation of ST segment by emergency teams directly on call have been analysed and several important patterns were identified. It has been revealed that according to some indicators of time, individual teams differed by 5-10 times. An emergency physician job seniority turned out to be an important factor. The general trend was the lowest time spent on individual tasks by doctors who had an average length of service in the ambulance (10 - 20 years), slightly higher - by doctors who had the longest work experience (over 20 years), and the largest - in doctors with the shortest work experience (up to 10 years). The differences between the senior and middle groups were less significant than between the junior and middle groups. Conclusions. The results obtained indicate significant variability in the implementation of protocol items in different emergency teams. A longer time to perform protocol items in the group with long job seniority may be related to the doctors' age perculiarities (the average age is 57 y.o., with the presence of people over 70 y.o.). The longest execution time is in the group with the shortest experience in the emergency medical service. This naturally reflects the lack of experience and a greater number of diagnostic and treatment errors.